2015
DOI: 10.3892/mmr.2015.3164
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in enhancer of zeste homolog 2, matrix metalloproteinase-2 and tissue inhibitor of metalloproteinase-2 expression are associated with ex vivo and in vitro bone metastasis in renal cell carcinoma

Abstract: Abstract. Renal cell carcinoma (RCC) has a high potential for bone metastasis; however, the molecular mechanisms underlying this metastasis have remained to be elucidated. The present study aimed to explore the expression levels of enhancer of zeste homolog 2 (EZH2), matrix metalloproteinase-2 (MMP2) and tissue inhibitor of metalloproteinase-2 (TIMP2) as determinants of RCC-associated bone metastasis. Their expression was evaluated in a newly generated RCC cell subline that has a high potential for bone metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have indicated the critical roles of MMP-2 in bone metastasis in various tumors. MMP-2 expression is contributed to matrix degradation and osteolytic bone metastasis in many tumors such as prostate cancer [34], breast cancer [35, 36], and renal cell carcinoma [37]. To explore the role of TSP-2/MMP-2 axis in bone metastasis of prostate cancer, we performed mouse models of bone metastasis by intratibial injection of cancer cells, and the bone metastasis was then detected by bioluminescence imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated the critical roles of MMP-2 in bone metastasis in various tumors. MMP-2 expression is contributed to matrix degradation and osteolytic bone metastasis in many tumors such as prostate cancer [34], breast cancer [35, 36], and renal cell carcinoma [37]. To explore the role of TSP-2/MMP-2 axis in bone metastasis of prostate cancer, we performed mouse models of bone metastasis by intratibial injection of cancer cells, and the bone metastasis was then detected by bioluminescence imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 80 ] explored the expression levels of enhancer of zeste homolog 2 (EZH2), matrix metalloproteinase-2 (MMP2) and tissue inhibitor of metalloproteinase-2 (TIMP2) as determinants of RCC-associated bone metastasis. The EZH2 and MMP2 proteins were more expressed in tissues of patients with RCC bone metastasis.…”
Section: Molecular Mechanisms Of Rccmentioning
confidence: 99%
“…The TIMP2 promoter was also highly methylated in ACHN-BO5 cells, an ACHN cell subline with high potential of bone metastasis, compared to in ACHN cells. The upregulation of EZH2, MMP2 and TIMP2 expressions correlated with RCC metastasis to bone tissues ex vivo and in vitro [ 80 ].…”
Section: Molecular Mechanisms Of Rccmentioning
confidence: 99%
“…5B). These results suggested that PRR11 contributed to OC cell proliferation, partly by affecting the [11]. Activated MMP2 degrades extracellular matrix (ECM) components to allow cancer cell expansion without resistance, whereas TIMP-2 is a specific inhibitor of MMP2 [12].…”
Section: Expression Of C-myc Cyclin D1 Mmp2 and Timp-2 Mediated Bymentioning
confidence: 99%